The Influence of Green Hrm and Responsive Boundary-Spanning on Worker Productivity Mediated By Green Innovation in Five-Star Hotels in Tabanan - Prasetya, Gusti Putu Ngurah Rama; Emilisa, Netania; Mumtazah, Kirana Ainayya; Gi, Lee Soo (International Journal of Environmental, Sustainability, and Social Science, 2026)
The growth of the hospitality industry in Bali, particularly five-star hotels in Tabanan, requires improvements in employee productivity through sustainable management practices. This study aims to analyze the influence of Green Human Resource Management (Green HRM) and responsive boundary-spanning on worker productivity, with green innovation as a mediating variable. This quantitative research used survey data collected from 200 employees of five-star hotels in Tabanan through a Likert-scale questionnaire. Data were analyzed using Structural Equation Modeling (SEM) to test the relationships among the variables. The results indicate that Green HRM and responsive boundary-spanning have a significant positive effect on green innovation and worker productivity. In addition, green innovation is found to mediate the relationship between Green HRM and worker productivity, as well as between responsive boundary-spanning and worker productivity. These findings affirm that environmentally oriented HR practices, the organization’s ability to respond to external dynamics, and the adoption of green innovation are strategic factors in strengthening operational efficiency and hotel competitiveness. This study provides theoretical and practical contributions for the hospitality industry in developing sustainability policies that are oriented toward employee performance.